Chapter Il test di associazione implicita (IAT) per il cambiamento climatico. Una revisione sistematica PRISMA - Fiorenza, Maria (Studies on Adult Learning and Education, 2022)
The global environmental concerns that affect our planet require immediate action. In order to better understand the psychological dynamics underlying the adoption of pro-environmental behaviors, the research has directed increasing attention to the implicit (unconscious) psychological antecedents (attitudes) of sustainable behaviors, which have been adopted against climate change. The objective of this systematic review is to examine and to summarize the state-of-the-art in the field of the relationship between implicit attitudes towards climate change measured through the Implicit Association Test (IAT), and explicit attitudes, beliefs, and identity toward climate change. Based on PRISMA guidelines, a structured electronic literature search of Google Scholar, PsycInfo, PubMed, Science Direct, PsycArticles, Sociological Abstracts, and Academic Search Complete was conducted. Of the 943 abstracts screened, only 18 studies met the inclusion criteria. Most studies testified independence between implicit and explicit attitudes towards climate change (absence of correlation). Despite this, implicit attitudes still predicted pro-environmental identity, while contradictory results appeared with beliefs. This highlights the urgency of promoting new research to understand on a deeper level dynamics involving implicit attitudes.